2013
DOI: 10.7546/cr-2013-66-7-13101331-14
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Entomophaga maimaiga Humber, Shimazu and Soper (Entomophthorales) for Suppressing Lymantria dispar (Linnaeus) Outbreaks in Bulgaria

Abstract: The Asian fungal entomopathogen Entomophaga maimaiga was first introduced in Bulgaria for biological control of gypsy moth, Lymantria dispar, in 1999 and the first epizootics in gypsy moth populations were observed in 2005. Six introductions of E. maimaiga in oak forests with heavy L. dispar infestations were conducted from 2008 to 2011 in different regions of the country, including Nova Zagora, Gorna Oryahovitsa, Popovo, Targovishte and Staro Oryahovo. As a result of these introductions, host density was decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…Surveys conducted at release sites during subsequent years confirmed successful transmission of the pathogen to the Bulgarian populations of L. dispar. The first epizootics by this fungus in gypsy moth populations were observed in 2005 (Pilarska et al 2006(Pilarska et al 2013Georgiev et al 2013). Since 2011, the fungus has been recorded in several countries of Central and Southeastern Europe (Kereselidze et al 2011;Georgiev et al 2012;Tabaković-Tošić et al 2012;Hrašovec et al 2013;Csóka et al 2014;Zúbrik et al 2014;2016;Hoch et al 2019).…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…Surveys conducted at release sites during subsequent years confirmed successful transmission of the pathogen to the Bulgarian populations of L. dispar. The first epizootics by this fungus in gypsy moth populations were observed in 2005 (Pilarska et al 2006(Pilarska et al 2013Georgiev et al 2013). Since 2011, the fungus has been recorded in several countries of Central and Southeastern Europe (Kereselidze et al 2011;Georgiev et al 2012;Tabaković-Tošić et al 2012;Hrašovec et al 2013;Csóka et al 2014;Zúbrik et al 2014;2016;Hoch et al 2019).…”
Section: Fungal Infectionsmentioning
confidence: 99%
“…The successful introduction of E. maimaiga into North American populations of L. dispar inspired its introduction into Bulgaria in 1999 [119]. Surveys conducted in subsequent years confirmed that the pathogen was successfully established and the first epizootics of E. maimaiga in L. dispar populations were observed in 2005 [120,121,122]. Since 2011, the fungus has been recovered in several countries of central and southeastern Europe [123,124,125,126,127,128,129].…”
Section: Microbial Control Of Invasive Pests With Entomopathogenicmentioning
confidence: 99%
“…However, only a few entomophthoralean fungi have been successfully manipulated to control harmful insects. Examples include the application of Zoophthora radicans to target exotic aphids in Australia [ 30 ] and the introduction of Entomophaga maimaga to control gypsy moths in Bulgaria [ 31 ]. Epizootics caused by Neozygites are an integral part of cassava green mite control, allowing farmers to reduce the extent and costs of pesticide use [ 30 ].…”
Section: How Do Entomophthoralean and Ascomycete Entomopathogens Compmentioning
confidence: 99%